ग्राम डॉग में सामाजिक एवं सांस्कृतिक परम्पराओं का जीविकोपार्जन तथा पर्यावरण पर प्रभाव का अध्ययन: The Impact of Social and Cultural Traditions on Livelihood and Environment in Rural Areas (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Culture is the social behavior and norms found in human societies. Culture is considered a central concept in anthropology encompassing the range of phenomenon that are transmitted through social learning in human societies these includes expressive forms like art, music, dance, ritual and technologies like tool usage , cookery, shelter and clothing. A person’s livelihood refers to their means of securing the basic necessities food, water, shelter, and clothing of life. Livelihood is defined as a set of activities performed to live for a given life span. Involving securing water, food, fodder, medicine, shelter, clothing and the capacity of acquire above necessities working either individually or as a group. During our investigation we find that social and cultural traditions of this area are very strong and these are beneficial for the society either ecologically as well as a means of livelihood. Due to the time, money, energy and other constraints the purposed study was delimited to the village Dang, Rankandiyal, Bonga, and Mulana. In the present investigation, a sample of 75 was selected randomly. The questionnaire and interview was used for collection of data. The data arranged into tables and was calculated. The data was analyzed and interpreted using percentage technique to achieve the objectives and verifying the hypothesis of the study. During our investigation we find that social and cultural traditions of investigated area are important for livelihood as well as for environment.